2016
DOI: 10.1186/s40478-016-0282-y
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected partial correction of metabolic and behavioral phenotypes of Alzheimer’s APP/PSEN1 mice by gene targeting of diabetes/Alzheimer’s-related Sorcs1

Abstract: IntroductionInsulin resistance and type 2 diabetes mellitus (T2D) are associated with increased risk for cognitive impairment, Alzheimer’s disease (AD) and vascular dementia. SORCS1 encodes a protein-sorting molecule genetically linked to both T2D and AD. The association of SORCS1 with both AD and T2D is sexually dimorphic in humans, with both disease associations showing more robust effects in females. Based on published evidence that manipulation of the mouse genome combining multiple genes related to cerebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 71 publications
2
14
0
Order By: Relevance
“…A11 and OC oligomer strains are not consistently neurotoxic. As reported above and in one of our previous studies [ 41 ], we noted sex differences in Aβ and oligomer levels suggesting an earlier progression of the disease in female than male APP/PSEN1 mice.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…A11 and OC oligomer strains are not consistently neurotoxic. As reported above and in one of our previous studies [ 41 ], we noted sex differences in Aβ and oligomer levels suggesting an earlier progression of the disease in female than male APP/PSEN1 mice.…”
Section: Discussionsupporting
confidence: 89%
“…Immunohistochemical and biochemical characterization were performed as previously described [ 40 , 41 , 44 , 76 ]. For biochemical analysis, hemibrains were processed via differential detergent solubilization to produce TBS-soluble, Triton-X-soluble, and formic-acid soluble Aβ fractions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 Type 2 diabetes mellitus (T2DM) might also be a potential risk for MCI progressing into AD, by inducing vascular dysfunction and oxidative and inflammatory stress. 6 Many cognitive functions, such as learning and memory, mental flexibility, and mental speed, have also been proved to be impaired in patients with T2DM. 7 Some epidemiological studies demonstrated that T2DM was a risk factor for developing cognitive impairment and dementia, including AD.…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemical and biochemical characterization were performed as previously described (3,(189)(190)(191)(192). For biochemical analysis, hemibrains were processed via differential detergent solubilization to produce TBS-soluble, Triton-X-soluble, and formic-acid soluble Aβ fractions.…”
Section: Immunohistochemical and Biochemical Analysismentioning
confidence: 99%